Karakteristik Mikroemulsi a-Tokoferol pada Perbandingan Campuran Tiga Surfaktan Nonionik dan Lama Pengadukan - Sucitawati, Putu Ayu; Suhendra, Lutfi; Ganda Putra, G. P. (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 1 (2021): MaretDO - 10.24843/JRMA.2021.v09.i01.p04, 2021)
Microemulsions have thermodynamics and stable kinetics as carriers of ?-tocopherol compounds. This study aimed to know the effect of mixtures ratio of three nonionic surfactants and stiring time on the characteristics of ?-tocopherol microemulsion, as well as to obtain the best stiring time and mixture ratio of three nonionic surfactants to produce ?-tocopherol microemulsion. This experiment used a randomized block design with two factors. The first factor is the ratio of a mixture of three nonionic surfactants with Hydrophilic-Lipophilic Balance (HLB) 14.5. The second factor is stirring time. Data were analyzed using analysis of variance and continued with BNJ test. Test the effectiveness index to determine the best treatment. The results showed that the comparison of three surfactant mixtures, stirring duration and interaction between treatments significantly affected the characteristics of ?-tocopherol microemulsion. Comparison of the mixture of three surfactants Tween 80: Span 80: Tween 20 (v / v%) HLB 14.5 consisting of F2 (89,5 : 5,5 : 5) and 4 minutes stirring time is the best treatment for the characteristics of ?-Tocopherol microemulsion. The best treatment has the characteristics of ?-tocopherol microemulsions namely transparent appearance, stable to centrifugation (4500 rpm), pH (4.5; 5.5 and 6.5) and dilution (1: 9, 1:49 and 1:99) with Turbidity index values ??are below 1 percent. Microemulsion turbidity index values ??before and after centrifugation were 0.19 percent and microemulsion turbidity at pH 4.5 and 1: 9 dilution were 0.11 percent. Keywords: microemulsion, stirring time, surfactan non ionic, ?- Tocoferol